Prognostic factors and the impact of frontline therapy in peripheral T-cell lymphoma: 10 years of 'real-world' experience from Western Australia. Issue 14 (6th December 2019) - Kuzich, James A.; Hutchison, Andrew P.; Lim, Kenneth J. C.; Smallbone, Portia; Denning, Kate; Wright, Matthew P.; Cull, Gavin; Leahy, Michael F.; Joske, David J. L.; Radeski, Dejan; Purtill, Duncan
Abstract: We present an analysis of 98 consecutive patients with peripheral T-cell lymphoma (PTCL) treated over a 10-year period within Western Australia. The most common frontline therapies were CHO(E)P (47%), HyperCVAD (21%), and reduced intensity therapy or supportive care alone (19%). Median and 4-year overall survival (OS) for the whole cohort were 1.59 years and 34%. Amongst CHO(E)P and HyperCVAD-treated patients, elevated LDH, advanced stage, IPI >1, and non-ALK + ALCL histology predicted inferior progression-free survival (PFS). Inferior OS was predicted by elevated LDH, age >60, IPI >1, and non-ALK + ALCL histology. Response rates and PFS were not significantly different between patients treated with CHO(E)P or HyperCVAD. OS was longer in the HyperCVAD group, however this was not significant on multivariable analysis and appears to relate to the younger age and more aggressive therapy at relapse in this group. Our data confirmed the prognostic utility of the IPI in patients with PTCL and do not demonstrate a clear benefit of HyperCVAD.